Knowledge diffusion at a major central European automotive supplier - Neves, Inês Silva (2022)
Diffusion of knowledge is a topic approached by modern economy to reach and sustain competitive advantage. As the environment is more uncertain, it is essential organisations learn to deal with new environmental changes as a consequence of Industry 4.0. The purpose of this project is to assess the adequacy of valuable knowledge diffusion in organisations during the implementation of Industry 4.0 principles and technologies. This diffusion is implemented in automotive businesses reaching an improvement of communication and production processes and consequently the productivity. This project establishes a case study, was adopted by an automotive industry Group focusing in promotion of knowledge diffusion and Industry 4.0 implementation among various stakeholders of the same company. The processes were analysed using observation, unstructured interviews and focus groups. The proposed challenge was to study how to apply Industry 4.0 to improve relevant knowledge sharing processes within the company. Regarding the needs and challenges identified, the best approach was to develop a communication channel which aligns the knowledge between all stakeholders. To link the two departments, recognize the value of an invention and achieve an innovation, some improvements were suggested and a new mean of communication was developed. The created product have not already been implemented due to time required, stakeholders busy schedule and R&D work dependability. With the proposed solution, the company will overcome the identified communication challenge and reduce the loss of important knowledge to maintain their progress.